1992
DOI: 10.1126/science.1411541
|View full text |Cite
|
Sign up to set email alerts
|

Demography of Genotypes: Failure of the Limited Life-Span Paradigm in Drosophila melanogaster

Abstract: Experimental systems that are amenable to genetic manipulation can be used to address fundamental questions about genetic and nongenetic determinants of longevity. Analysis of large cohorts of ten genotypes of Drosophila melanogaster raised under conditions that favored extended survival has revealed variation between genotypes in both the slope and location of age-specific mortality curves. More detailed examination of a single genotype showed that the mortality trajectory was best fit by a two-stage Gompertz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
221
6
4

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(238 citation statements)
references
References 11 publications
7
221
6
4
Order By: Relevance
“…Brooks et al (1994) demonstrated that mortality rate in an isogenic population of the nematode Caenorhabditis elegans showed a less-distinct plateau than in a genetically heterogeneous population, but Vaupel et al (1994) were quick to point out that the isogenic line was grown at a higher temperature and in higher food concentration than the heterogeneous line, greatly complicating the interpretation of the mortality patterns. In addition, isogenic versus heterogenous populations of Drosophila melanogaster do not consistently show these same patterns (Curtsinger et al, 1992;Fukui et al, 1996). Furthermore, although the relevance of individual environmental heterogeneity to late-life mortality rates is extremely difficult to test effectively (Curtsinger et al, 1992;Fukui et al, 1993;Vaupel and Carey, 1993), an intricate experiment by Khazaeli et al (1998) found no evidence to support the hypothesis that environmental heterogeneity among individual flies is a primary factor in determining late-life mortality rates.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Brooks et al (1994) demonstrated that mortality rate in an isogenic population of the nematode Caenorhabditis elegans showed a less-distinct plateau than in a genetically heterogeneous population, but Vaupel et al (1994) were quick to point out that the isogenic line was grown at a higher temperature and in higher food concentration than the heterogeneous line, greatly complicating the interpretation of the mortality patterns. In addition, isogenic versus heterogenous populations of Drosophila melanogaster do not consistently show these same patterns (Curtsinger et al, 1992;Fukui et al, 1996). Furthermore, although the relevance of individual environmental heterogeneity to late-life mortality rates is extremely difficult to test effectively (Curtsinger et al, 1992;Fukui et al, 1993;Vaupel and Carey, 1993), an intricate experiment by Khazaeli et al (1998) found no evidence to support the hypothesis that environmental heterogeneity among individual flies is a primary factor in determining late-life mortality rates.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, isogenic versus heterogenous populations of Drosophila melanogaster do not consistently show these same patterns (Curtsinger et al, 1992;Fukui et al, 1996). Furthermore, although the relevance of individual environmental heterogeneity to late-life mortality rates is extremely difficult to test effectively (Curtsinger et al, 1992;Fukui et al, 1993;Vaupel and Carey, 1993), an intricate experiment by Khazaeli et al (1998) found no evidence to support the hypothesis that environmental heterogeneity among individual flies is a primary factor in determining late-life mortality rates. In another experiment, Khazaeli et al (1995b) seemingly demonstrated environmental heterogeneity for stress resistance by subjecting genetically homogenous populations to a 24-hr heat stress and comparing their poststress mortality patterns to control lines; however, this paper was later retracted after new research revealed that the experimental method was flawed Khazaeli et al, 1997;Tatar et al, 1997).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In some other organisms, such as Pacific salmon and the marsupial Antechinus , there is a spectacular period of aging which proceeds so rapidly that no individuals survive after the aging phase. But in many animals, we now know, there is a period after aging during which mortality and fecundity plateau (Carey et al ., 1992;Curtsinger et al ., 1992;Vaupel et al ., 1998;Rauser et al ., 2003). That is, aging stops, and a new phase of life begins Rauser et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%